'Blocked at every level': criminal justice system professionals' experiences of including people with intellectual disabilities within a targeted magistrates' court. Issue 3 (28th March 2020) - Chadwick, Darren David; Wesson, Caroline
Abstract : Purpose: Mental health courts (MHCs) may enable better support for people with intellectual disabilities (ID) within the criminal justice system (CJS) but little evaluative empirical evidence is available regarding their operation. The purpose of this paper is to explore professional perceptions of the challenges of including people with ID in a targeted services court (TSC) designed for people with mental health issues and ID. Design/methodology/approach: Information was gathered, via interviews and focus groups, from 46 professionals working with people with mental health issues and ID within the TSC. Data were analysed by using thematic network analysis. Findings: Findings highlight the neglect and lack of inclusion of people with ID within the TSC processes, with challenges in identifying people with ID, stakeholder awareness, inconsistent adapting of practices for people with ID and information transfer underpinned by the involvement of numerous organisations with differing agendas. Research limitations/implications: Although valued, development of a TSC, including people with ID, was a challenging endeavour and may reflect societal and institutional neglect of people with ID, recommendations are provided. Originality/value: This study adds to the few investigations that have considered the process of including people with ID in a TSC from the perspective of those working in the CJS.